CALCULATION OF THE COST OF THE DEVELOPED FUNCTIONAL DRINK BASED ON MATCHA TEA - V. S. Paukova (Современная наука и инновации, 2023)
The purpose of the work is to calculate the cost of the developed functional drink based on mast tea. Matcha is a Japanese powdered green tea. At the first stage, the total investment volume is estimated: the prices for equipment and installation are summed up. The main stage is the calculation of the cost of the developed functional drink based on matcha tea. To obtain the cost index, the costs of raw materials, containers and packaging for the year are calculated. Next, the amount of water costs for various production needs is calculated, as well as the electricity consumed by the equipment. At the next stage, staff salaries are calculated, which consists of the main and additional wages of the workers of the enterprise. The calculation is made with respect to such concepts as: working time fund, working time balance. The payroll expenses per 1 liter of finished products were calculated. It was important to take into account mandatory social payments, social insurance contributions. Next, the amount of depreciation deductions was calculated. One of the most important indicators for calculating the cost price is rent. It is supposed to lease land with a production facility located on it. Then the indicator was calculated – other costs. These costs were approximately assumed to be equal to 2% of the cost of raw materials. The value of the production cost of products is revealed. The total cost of production was calculated as the sum of the production cost and, previously found, non-production costs. The structure of the total cost for a different volume of the drink is calculated and presented in tabular data. Next, the value of the profitability of the finished product was determined. In addition, the efficiency of the production of matcha tea drink was determined based on the assessment of the payback period. According to the results, it turned out that the company will pay off in less than 4 years. The calculation showed that the implementation of the investment project is expedient. The positive value of accumulated cash flows means that we have additional opportunities. Due to the fact that this investment project is financed by borrowed funds, the amount of cash income that the firm can use to repay the loan and pay interest on the loan was calculated. As a result of the feasibility study of the project, the following values were calculated: the cost of the annual finished product of 14,600,466 rubles; the selling price of the enterprise of the annual finished product of 2101,9700 rubles, or 57.5 rubles for one bottle of a 500 ml drink; the net profit of the enterprise for the year of 6419,230 rubles; the cost of 1 ruble of marketable products – 0.80 rubles. Thus, the developed project can be evaluated as effective. The product produced is a functional drink containing vitamins, minerals, and antioxidants. Due to the usefulness of the drink, it will be in demand among consumers. In addition, the profitability of the drink is 16%, which indicates the efficiency of the enterprise.